HUBUNGAN ANTARA POSTUR KERJA BERDIRI DENGAN KELUHAN NYERI KAKI PADA PEKERJA AKTIVITAS MEKANIK SECTION WELDING DI PT. X - Siska Maulina Anggrianti; Bina Kurniawan; Baju Widjasena (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Leg pain is a discomfort feeling in the foot or leg area caused by pressure on the sciatic nerve, muscle tension or poor blood supply due to continuous and excessive physical activity. Leg pain is also frequently caused by the body posture while working, such as standing for a long time. The research aimed to find out the correlation between standing working posture and leg pain among the mechanical workers in the welding section of PT. X. The method of this research was observational analytic with cross sectional approach. The sample of this study was the total population that consists of 30 people. The data were collected by using questionnaires and REBA to measure work posture and analyzed by Chi Square. The result showed that the majority of workers had complaints of the leg pain with light category amounted to 53.3% and 46.7% of the workers are in the medium category for standing posture. The statistical results showed that there is a correlation between standing working posture (sig = 0,029) and the occurrence of the leg pain among the mechanical workers in welding section at PT. X. It is recommended for companies to repair workstations, particularly on desks, make joint sports programs regularly, create health screening programs and provide information about work postures and the importance of ergonomics during briefings before work. Workers are advised to do stretching before working, when the body feels tired, in the middle of working, after working and also to change body position.